Bibliometric Analysis of Articles on Disaster Victim Identification - İğde, Emre Nuri; Alemdar, Muhammed Zeyit; Akçan, Ramazan (The Bulletin of Legal Medicine, 2024)
Objective: In this study, it was aimed to determine current study topics and changing dynamics in the field of Disaster Victim Identification by conducting a bibliometric analysis of articles in the international literature.Methods: In the Web of Science database, the words “disaster victim identification”, “DVI” and “mass disaster” were searched in the titles and keywords of the publications and the articles in the literature were evaluated. The study contained 190 articles which fulfilled the criteria of being indexed in SCI-E, SSCI, or ESCI, having the research area “medicine legal”, being of document type “article”, and being in English language were included in the study.Results: The first paper was published in 1971, and the peak year for publications was 2011. Australia was the most productive country in this field with 42 publications. The articles received a total of 2,664 citations over the years, with the highest number of citations occurring in 2021. These articles were published in 15 journals, and Forensic Science International was the leading journal in this field with 55 articles. When the top 10 most cited articles were examined, it was observed that the studies covered various fields such as genetics, anthropology, radiology and odontology.Conclusion: This study is the pioneering bibliometric analysis of disaster victim identification articles. By assessing publication characteristics, international collaboration, and co-citation analysis, we’ve shed light on the latest research trends in this field. Consequently, we believe our work offers valuable insights to researchers in forensic medicine and forensic sciences.
Keywords: Forensic Medicine; Bibliometric Analysis; Disaster Victim Identification